The visual multiplicity of films and its implications for audio description: A case study of the film What Dreams May Come - Maszerowska, Anna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
Multilingualism in film is largely understood in terms of verbal communication. However, multiplicity also strongly manifests itself at the level of visual narration. The many codes within the cinematographic language encourage a broadening of the concept of multilingualism beyond the spectrum of words alone. This article examines the implications of visual multiplicity for media accessibility and, in particular, for audio description. Taking as a starting point Chaume’s (2004a, 2004b) classification of signifying codes of cinematographic language, we carry out a detailed analysis of the film What Dreams May Come (1998), discuss the composition of the filmic image and suggest strategies for achieving a successful descriptive integration of the visual and the verbal.